2020
DOI: 10.1093/mnras/staa871
|View full text |Cite
|
Sign up to set email alerts
|

High-redshift cosmography: auxiliary variables versus Padé polynomials

Abstract: Cosmography becomes non-predictive when cosmic data span beyond the red shift limit z ≃ 1. This leads to a strong convergence issue that jeopardizes its viability. In this work, we critically compare the two main solutions of the convergence problem, i.e. the y-parametrizations of the redshift and the alternatives to Taylor expansions based on Padé series. In particular, among several possibilities, we consider two widely adopted parametrizations, namely y 1 = 1 − a and y 2 = arctan(a −1 − 1), being a the scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
87
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 78 publications
23
87
1
Order By: Relevance
“…This value is quite closer to that constrained by Capozziello et al. [75]. From a joint analysis of the H(z) data and the Pantheon compilation data, the Hubble parameter H 0 is obtained to be 69.36±1.42kms1Mpc1 which sits in a range middle to the observed Hubble tension.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This value is quite closer to that constrained by Capozziello et al. [75]. From a joint analysis of the H(z) data and the Pantheon compilation data, the Hubble parameter H 0 is obtained to be 69.36±1.42kms1Mpc1 which sits in a range middle to the observed Hubble tension.…”
Section: Discussionsupporting
confidence: 86%
“…Capozziello et al. [ 75 ] have also obtained a slightly larger value of j than the value predicted by concordance paradigm. Mukherjee and Banerjee in their work, [ 82 ] concluded that, any deviation of the jerk parameter from the ΛCDM value indicates an interaction between the dark energy and dark matter.…”
Section: Physical Behaviour Of Modelmentioning
confidence: 86%
See 1 more Smart Citation
“…Surely the parameters made out of even higher derivatives like snap (4th order derivative of a), crack (5th order derivative) etc. could well be evolving [78]. But we focus on j which is the evolution of q, the highest order derivative that is an observationally measured quantity.…”
Section: Discussionmentioning
confidence: 99%
“…3). As a well-known method in cosmology, cosmography method has been widely used in the literature [37][38][39][40][41][42][43][44][45][46][47]. This method was first proposed by [37] and [38] to distinguish between various dark energy models.…”
Section: Introductionmentioning
confidence: 99%